经微导管碘化油化疗药乳剂栓塞治疗原发性富血型非小细胞肺癌41例分析 (Zhongguo Fei Ai Za Zhi, 2010)
BACKGROUND AND OBJECTIVE: Transcatheter arterial chemotherapy and embolization is the main method in the treatment of lung cancer, but most of the reports do not study individually to small cell lung cancer (SCLC), non-small cell lung cancer (NSCLC), hypovascular and hypervascular lung cancer. The pre-embolization perfusion of hemotherapeutics is still being used routinely and seldom report to iodized oil embolization. The article summarized the quality of life after the treatment, clinical efficiency, survival time and complications to evaluate the clinical effect of primary hypervascular NSCLC treated with embolization of emulsion of chemotherapeutics and iodized oil. METHODS: The study totally analyzed 41 cases which confirmed by pathology and follow up study from January, 2008 to January 2009. The CT scan with Ⅳ contrast demonstrates over moderate enhanced lesion which indicate hypervascular. Within the 41 cases, 23 cases of central, 18 cases of peripheral. Suqamous carcinoma 21 cases, adenocarcinoma 15 cases and squamoadenocarcinoma 5 cases. Stage Ⅲb 34 cases, stage Ⅳ 7 cases. Superselective incubation with microcatheter under DSA, to embolize the capillary bed with liquefied iodized oil and the emulsion of pharmorubicin, to embolize the supply artery of the tumor with gelatin foam microparticle. The liquefied iodized oil 5 mL-10 mL, pharmorubicin 10 mg-30 mg. The longest follow up is 12 months and to compare with the references of 2007-2009. RESULTS: The KPS is widely acclaimed after the treatment (P < 0.05), no complete response (CR), 31 cases of partial response (PR), 7 cases of no change (NC) and 3 cases of progressive disease (PD), the total efficiency (CR+PR) is 75.6%. The clinical efficiency (CR+PR+NC) is 92.68%. 33 cases of total survival tome over 12 months (80.48%), Ⅲb stage 29/34 (85.29%), Ⅳ stage 4/7 (57.14%). 1 case with severe complication-spinal injury. CONCLUSION: To treat primary hypervascular NSCLC with simple embolization of emulsion of chemotherapeutics and iodized oil is very useful and can avoid the side effect of chemotherapeutics. The key point to avoid spinal injury and other severe complications is to distinguish the spinal aretery and intratumor AV fistula by using superselective incubation with microcatheter under DSA.